Towards Functional Safety in Drive-by-Wire Vehicles - Bergmiller, Peter Johannes (Springer International Publishing : Imprint: Springer, 2015)
This book presents approaches to address key challenges based on a vehicle level view and with a special emphasis on Drive-by-Wire systems. The design and testing of modern vehicle electronics are becoming more and more demanding due to increasing interdependencies among components and the safety criticality of tasks. The development towards Drive-by-Wire functionalities in vehicles with multiple actuators for vehicle control further increases the challenge. The book explicitly takes into account the interactions between components  and aims at bridging the gap between the need to generate additional customer benefits and the effort to achieve functional safety. The book follows a twofold approach: on the one side, it presents a toolchain to support efficient further development of novel functionalities for Drive-by-Wire vehicles. The toolchain comprises appropriate software tools and scaled and full-scale experimental vehicles. On the other side, development towards functionally safe and flexible Drive-by-Wire vehicles is addressed by proposing a top-down designed architecture for vehicle electronics that is enabled by suitable mechanisms. The resulting goal achievement with regard to functional safety is evaluated based on a novel hierarchical approach.